Maternal pre-pregnancy body mass index and weight gain during pregnancy in Asia - Inoue, Madoka; Binns, Colin (Nova Science Publishers, Inc, 2013)
Maternal Body Mass Index (BMI) before becoming pregnant and weight gain during pregnancy are indicators of a mother's nutritional status that influence her own health and her infant's growth. The development of the fetus is important in determining health during the perinatal period, through infancy and childhood, and into adult life. The health of mothers in the postpartum period and later in life may also be affected by nutritional status before and throughout pregnancy. The Institute of Medicine (IOM) has developed guidelines for weight gain during pregnancy which is based on empirical studies in the Western countries. Maternal BMI pre-pregnancy and gestational weight gain varies between countries and different cultures. Most Asian countries, except Taiwan and Japan, have adopted the guidelines on gestational weight gain from the IOM, or modifications of this guideline. Japan has its own guidelines for maternal weight gain during pregnancy which differs from other international recommendations. There are several guidelines for maternal weight gain during pregnancy in use in Japan, which differ from other countries. This may be due to the different historical background of health outcomes in the perinatal period and unique cultural beliefs about women's body shape in Japan. The WHO has recognised the difficulty of atten1pting to use the IOM guidelines in populations that are different from the USA and have recommended the development of new international guidelines.In developing recommendations for maternal weight gain during pregnancy, it will be necessary to include considerations of infant and maternal outcomes together with information on body composition and anthropological perspectives. In many Asian countries maternal pre-pregnancy BMI and weight gain during pregnancy is below the ranges used in the IOM guidelines. The classification of BM! developed by the WHO may not be suitable for pregnant women in Asian countries due to the ethnic variations in body composition. In Asia a secular trend in body weight is occurring with the resultant increase in rates of obesity. However in Japan, although it is an economically advanced country, there has been an increase in the prevalence of the 'underweight' category in BMI of women before pregnancy. The development and adoption of international guidelines will require extensive consultation and education to ensure their use in the region. In this chapter pre-pregnancy BMI, weight gain during pregnancy and the relevance of the IOM for the region particularly, focusing on Japan will be reviewed.